2020
DOI: 10.1038/s41419-020-2695-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Downregulation of RKIP promotes radioresistance of nasopharyngeal carcinoma by activating NRF2/NQO1 axis via downregulating miR-450b-5p

Abstract: Dysregulation of RKIP and NRF2 has been widely involved in the therapy resistance of multiple malignances, however, their relation and the corresponding mechanisms, especially in radiation response, have not been elucidated. In this study, we revealed that RKIP could negatively regulate the expression of NRF2 in nasopharyngeal carcinoma (NPC) cells. Depletion or ectopic expression of NRF2 countered the pro- or anti- radioresistant effects of RKIP knockdown or overexpression on NPC cells, respectively, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Intensity-modulated radiotherapy (IMRT) is the most prominently used technique for treating patients with NPC. Although IMRT significantly improves the survival rates and local control of NPC in patients, and reduces the toxicity levels ( 1 , 33 36 ), radioresistance is the primary cause for the failure of NPC treatment ( 37 ). In the present study, a radioresistant NPC cell model was established, termed 5-8F-R, to identify the key gene and miRNA involved in the acquisition of NPC radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) is the most prominently used technique for treating patients with NPC. Although IMRT significantly improves the survival rates and local control of NPC in patients, and reduces the toxicity levels ( 1 , 33 36 ), radioresistance is the primary cause for the failure of NPC treatment ( 37 ). In the present study, a radioresistant NPC cell model was established, termed 5-8F-R, to identify the key gene and miRNA involved in the acquisition of NPC radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated basal level of ROS and the migration ability in the cells after one radiation schedule (NF639R 40 Gy ) and the cells after two radiation schedule (NF639R). Compared with NF639R 40 Gy cells, NF639R cells displayed enhanced migration ability (Figure 5A,B) and lower basal level of ROS (Figure 5C,D), suggesting that two schedules of radiation (40 Gy/schedule) render NF639R cells more aggressive, Furthermore, we detected the expression of some genes including a positive prognostic indicator (Hoxd13), two inducers of radioresistance (Nqo1 and Aldh3a1) (37,38), one inducer of cell migration (Tgfbi) and two suppressors of cell migration (Sdpr and Klk10) using qPCR in NF639R 40 Gy cells and NF639R cells. The results showed that the expression of Aldh3a1, Tgfbi and Nqo1 were increased, but expression of Sdpr, Klk10 and Hoxd13 were decreased in both NF639R 40 Gy and NF639R cells.…”
Section: The Enhance Of Tumor Malignancy After Two Radiation Schedulesmentioning
confidence: 90%
“…Western blot was carried out as described previously by us [ 3 , 26 ]. Briefly, the total proteins were collected from RIPA cell lysis by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferation was analyzed using a CCK-8 kit (Beyotime, Shanghai, China) as our previous description [ 3 , 26 ]. The assay was performed three times in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation